2002
DOI: 10.1089/089277902760367412
|View full text |Cite
|
Sign up to set email alerts
|

Thermostasis during Laparoscopic Urologic Surgery

Abstract: It has been postulated that gaseous insufflation of the abdominal cavity results in temperature elevation, particularly in children, and that the use of heating blankets should be avoided during laparoscopic surgery. On review of the last 102 laparoscopic genitourinary cases, we conclude that the use of nonheated, nonhumidified carbon dioxide for insufflation during laparoscopic surgery under a general anesthetic results in mild hypothermia. The use of warming devices in this setting is both safe and appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Kaynan and associates 30 reported in a retrospective review of 102 laparoscopic urologic procedures in children on the prevention of intraoperative hypothermia using heating blankets. They showed that, in children, the use of nonheated, nonhumidified CO 2 for insufflation during laparoscopic surgery under general anesthesia results in mild hypothermia, necessitating prevention with external warming devices.…”
Section: Discussionmentioning
confidence: 99%
“…Kaynan and associates 30 reported in a retrospective review of 102 laparoscopic urologic procedures in children on the prevention of intraoperative hypothermia using heating blankets. They showed that, in children, the use of nonheated, nonhumidified CO 2 for insufflation during laparoscopic surgery under general anesthesia results in mild hypothermia, necessitating prevention with external warming devices.…”
Section: Discussionmentioning
confidence: 99%
“…The five cardinal perils of CO 2 pneumoperitoneum are abdominal compartment syndrome,[14] hypercarbia,[15] respiratory acidosis,[16] tissue desiccation and hypothermia. [1718] They together contribute significantly to several physiological changes [Figure 2]. For example, electrocardiograms (ECG) of children undergoing laparoscopic appendectomy showed significant QT dispersion and P-wave depression during CO 2 insufflation (QoE-C4).…”
Section: Discussionmentioning
confidence: 99%
“…An adverse effect of laparoscopy is the hypothermia caused by CO 2 insufflation at room temperature [15]. In our patients, normothermia was obtained by means of an external patient warming device.…”
Section: Discussionmentioning
confidence: 99%